Synthesis, characterization, and antimicrobial activity of silver nanoparticles derived from Mentha X piperita + Ocimum tenuiflorum: An in vitro study - L Harsha; Ravindra Kumar Jain; Arya S Prasad (Wolters Kluwer Medknow Publications, 2022)
The objective of the study was to synthesize silver nanoparticles using Mentha X Piperita (Mint) + Ocimum tenuiflorum (tulsi) and to confirm its size and shape. 0.5 mg of tulsi and 0.5 mg mint were diluted in distilled water (100 ml). The dissolved formulation was heated for 15 min at 70°C and filtered. The filtrate was homogeneously combined with 0.9 mg of silver nitrate to prepare nanoparticles of silver (AgNPs). The characterization of the obtained nanoparticle was done using transmission electron microscopy. Using agar disc diffusion assay, the antibacterial property was evaluated against common oral microbes at different concentrations. Silver nanoparticles showed excellent antimicrobial activity against Streptococcus mutans at 100 μL concentration. At 25 and 50 μL, all microbes showed similar extent of antimicrobial activity when quantified. Tulsi and mint prove to be effective in synthesizing silver nanoparticles that have good antimicrobial activity against oral microbes.